Cultural values, economic growth, and international IPO underpricing: evidence from Chinese companies - Geng, Peixuan; Tan, Qingmei (Journal of Business Economics and Management, 2021)
Listing markets have different cultural backgrounds and experience different economic development. This study examines the impact of cultural values and the moderating effect of economic growth on IPO underpricing issued by Chinese companies in different stock markets. Using a sample of 2429 IPOs issuing in four different stock markets for the 2000–2018 period, the results suggest that in markets with higher power distance or longer-term orientation, IPOs experience higher underpricing; in markets with higher uncertainty avoidance scores, masculinity, individualism, or indulgence, IPOs experience lower underpricing. The greater the multidimensional cultural distance is to the Chinese A-share market, the less underpricing IPOs experience. Economic growth has a significant moderating effect, thereby intensifying or restraining the relationship between culture and IPO underpricing. The additional analysis considering cross-listing companies, and the robustness tests considering alternative measures of culture further support the above conclusions. This study highlights the cultural and economic factors motivating IPO underpricing, can help managers select listing markets from cultural and economic perspective.